A Multifunctional Silly‐Putty Nanocomposite Spontaneously Repairs Cathode Composite for Advanced Li−S Batteries. (16th October 2018) - Chang, Zhi; He, Yibo; Deng, Han; Li, Xiang; Wu, Shichao; Qiao, Yu; Wang, Pengfei; Zhou, Haoshen
Abstract: Although lithium–sulfur batteries have been regarded as one of the most promising candidates for high efficient energy storage devices, however, their practical application are still hindered by the notorious "shuttle effect" and instability of cathode structure during cycling. In this work, conductive reduced graphene oxides nanosheets added–putty (rGO–putty ) adaptive functional interlayer is designed to effectively suppress the diffusion of polysulfides while simultaneously promoted the dynamic protection of the whole cathode structure during cycling. Consequently, largely suppressed polysulfides diffusion combined with the greatly enhanced cathode stability is achieved while the all‐around conductive protecting layer is formed benefited from the viscoelasticity property of rGO–putty. As a result, a capacity of 586 mAh g −1 is demonstrated after long‐cycling term of 1000 cycles and high cycling stability of only 0.03% capacity decay per cycle is exhibited. The largely enhanced electrochemical performance suggests the important role of the rGO–putty in suppressing the "shuttle effect" and maintaining the integrity of the cathode material. Abstract : Self‐healing conductive polymer reduced graphene oxide–Silly Putty enables effective suppression of "shuttle effects" while spontaneously forming all‐around conductive protecting layer on the surface of the cathode and repairs the mechanical/structure damages of the cathode in Li−S batteries during cycling is reported. As a result, the G‐SP added cell delivers a capacity of 586 mAh g −1 after 1000 cycles.